INFLUENCE OF BIOPSYCHOSOCIAL FACTORS ON ADAPTIVE COPING STRATEGIES AMONG COVID-19 SURVIVORS IN SURAKARTA - Pramulawati, Devi Anggraeni; Fanani, Mohammad; Setyaningrum, Rohmaningtyas Hidayah (Fakultas Kedokteran Universitas Jenderal Achmad Yani, 2025)
The COVID-19 pandemic has unleashed a profound psychological crisis, markedly increasing rates of depression, anxiety, loneliness, and PTSD, especially among young adults, women, racialized communities, and individuals with lower education and income. Effective coping strategies like positive reframing, humor, and acceptance have been linked to improved mental health outcomes, while maladaptive coping correlates with worsening psychosocial symptoms. This study explores the biopsychosocial factors that shape adaptive coping mechanisms in COVID-19 survivors. Using a cross-sectional design and quantitative approach, data were analyzed using logistic regression analysis. The study involved 378 COVID-19 survivors from Surakarta, who completed both online (via Telegram and WhatsApp) and offline questionnaires between November 2022 and January 2023. The sample predominantly consisted of women (73%, n=276) aged 18-40 years (89.7%, n=339), with a high prevalence of adaptive coping mechanisms (97.1%, n=367). Results revealed that gender (p=0.029, B=-1.497), history of mental disorders (p=0.039, B=-2.002), and alcohol/substance use (p=0.027, B=-2.572) had a significant influence on adaptive coping. These findings suggest that gender, mental health history, and substance use as crucial factors influencing adaptive coping among COVID-19 survivors. Keywords: adaptive coping, biopsychosocial factors, COVID-19 survivors DOI :10.35990/mk.v8n4.p378-388